2017
DOI: 10.3855/jidc.9132
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of macrolide resistant Group A streptococci from Puducherry, India

Abstract: Introduction: In penicillin allergic patients, macrolides are the most commonly used antibiotics for treating streptococcal infections, irrespective of the higher resistance rates. The objective of this study was to evaluate the comparative prevalence, phenotypes, and genetic determinants of macrolide resistance and associated emm types among different clinical isolates of Streptococcus pyogenes. Methodology: A total of 173 Streptococcus pyogenes isolates were examined for macrolide resistance phenotype by dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
1
Order By: Relevance
“…The pattern of antibiotic resistance fluctuates worldwide. In a study in India, 51.4% of the GAS isolates were resistant to erythromycin, of which, 65.1% harbored ermB and 32.5% harbored mef A as the only genes resistant to macrolides, while 2.2% harbored both ermB and mefA [ 8 ]. The resistance rate of erythromycin and clindamycin in Korea decreased from 51.0 and 33.7% in 2002 to 9.8 and 8.8% in 2004, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of antibiotic resistance fluctuates worldwide. In a study in India, 51.4% of the GAS isolates were resistant to erythromycin, of which, 65.1% harbored ermB and 32.5% harbored mef A as the only genes resistant to macrolides, while 2.2% harbored both ermB and mefA [ 8 ]. The resistance rate of erythromycin and clindamycin in Korea decreased from 51.0 and 33.7% in 2002 to 9.8 and 8.8% in 2004, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Penicillin is the preferred clinical treatment of GAS infection, while erythromycin is the first alternative antibiotic for patients allergic to penicillin, followed by clindamycin. The resistance rate to macrolidesis gradually increasing, which might be related to the overuse of such antibiotics [7,8]. In our previous study, 95 isolates were recovered from suppurative tonsillitis, acute glomerulonephritis, scarlet fever and streptococcal dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…had both ermB and mefA [8]. The drug resistance rate of erythromycin and clindamycin in Korea decreased from 51.0% and 33.7% in 2002 to 9.8% and 8.8% in 2004, respectively.…”
Section: Emm Type and Superantigen Distributionmentioning
confidence: 97%
“…Penicillin is the preferred clinical treatment of GAS infection, while erythromycin is the first alternative antibiotic for patients allergic to penicillin, followed by clindamycin. The drug resistance rate to macrolides, used as alternative antibiotics, is gradually increasing, which might be related to the overuse of such antibiotics [7,8]. Our previous study has shown high frequency of resistance to erythromycin, clindamycin, and tetracycline in GAS [9].…”
Section: Introductionmentioning
confidence: 99%
“…Penicillin is the preferred clinical treatment of GAS infection, while erythromycin is the first alternative antibiotic for patients allergic to penicillin, followed by clindamycin. The drug resistance rate to macrolides, used as alternative antibiotics, is gradually increasing, which might be related to the overuse of such antibiotics [7,8]. In our previous study, 95 isolates were recovered from suppurative tonsillitis, acute glomerulonephritis, scarlet fever and streptococcal dermatitis.…”
mentioning
confidence: 99%